Pengaruh Critical Thinking dan Motivasi Belajar terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Hindu Kelas X di SMA Negeri 2 Denpasar Tahun Ajaran 2022/2023 - I Gusti Made Kusuma Dhana; Ida Ayu Windu Artesari (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
Education in the current era is a necessity for the nation and for humanity itself, as it provides individuals with guidance to further develop their potential. Especially in the 21st century, which is full of fundamental changes, the development of students' critical thinking skills in learning is an effort to increase motivation towards student learning outcomes within the education system of the Industrial Revolution 4.0 era. This research collected data by distributing questionnaires to 217 samples. The results showed that both critical thinking and learning motivation were in the high category, and learning outcomes were in the good category. The analysis of the effect of critical thinking on student learning outcomes showed that critical thinking contributed 74.3%. Learning motivation contributed 73.7% to student learning outcomes. The multiple linear regression analysis results indicated that critical thinking and learning motivation influenced student learning outcomes in the Hindu Religious Education subject for 10th-grade students at SMA Negeri 2 Denpasar in the 2022/2023 Academic Year, with a total contribution of 60.5%.